Knowledge, Attitudes, and Practices of Hypertensive Patients Towards Stroke Prevention Among Rural Population in Saudi Arabia: A Cross-Sectional Study - Fahad M. Alhowaymel PhD, RN; Mohammed A. Abdelmalik PhD, RN; Almoez M. Mohammed MSN, RN; Mohamaed O. Mohamaed PhD, RN; Atallah Alenezi PhD, RN (SAGE Publishing, 2023)
Introduction Stroke is a significant health problem and is considered one of the leading causes of mortality and permanent disability worldwide. Hypertension is a primary risk factor for stroke. Thus, hypertensive patients' knowledge, attitudes, and practices (KAP) are essential in preventing stroke. Objective To examine hypertensive patients' KAP towards stroke prevention among rural population in Saudi Arabia. Methods The study utilized a cross-sectional design. The data were collected using a convenience sampling technique from hypertensive patients in the northwestern rural areas of Riyadh Province. A self-administered questionnaire was adapted from the Stroke Recognition Questionnaire (SRQ) and utilized to assess KAP towards stroke prevention among rural hypertensive patients. The STrengthening of the Reporting of OBservational studies in Epidemiology (STROBE) checklist was used to report the study. Results A total of 196 hypertensive patients participated in the study. The total mean scores categorization into three quartiles showed that most respondents had poor levels of KAP towards stroke prevention. Weak positive correlations were found between KAP of patients. There were statistically significant differences between respondents' attitudes and practices with their age, education, marital status, and occupational status. Discussion This study denoted poor levels of KAP towards stroke prevention among hypertensive patients living in rural areas. This study showed the importance of further considering rural population by which improving their health and quality of life. Extending health educational programs and behavior-changing strategies to rural areas is essential to increase hypertensive patients and general public awareness about their stroke prevention and other health-related concerns.